2012
DOI: 10.1097/ftd.0b013e318261c240
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling of Risperidone and 9-Hydroxyrisperidone to Estimate CYP2D6 Subpopulations in Children and Adolescents

Abstract: AIM The study aims were to characterize risperidone and (±)-9-hydroxyrisperidone pharmacokinetic variability in children and adolescents and to evaluate covariate effects on pharmacokinetic parameters. METHODS Steady-state samples were drawn at pre-dose, 1, 2, 4, and 7 hours post-dose; CYP2D6 genotypes were available for 28 subjects. A non-linear mixed-effects model (NONMEM®) modeled the pharmacokinetics of risperidone and (±)-9-hydroxyrisperidone; covariates included age, weight, sex, and CYP2D6 phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 41 publications
3
36
1
Order By: Relevance
“…This quantitative ‘bottom-up’ approach includes physiologically-based in vitro – in vivo extrapolation (IVIVE) and has gained momentum due to our increased understanding of the contributing factors (e.g., physical chemistry, systems physiology and pharmacogenetics) and advances in quantitative modeling using mechanistic models. 2,33,5462 …”
Section: Physiology- and Population-based Pharmacokinetic Modeling (Pmentioning
confidence: 99%
“…This quantitative ‘bottom-up’ approach includes physiologically-based in vitro – in vivo extrapolation (IVIVE) and has gained momentum due to our increased understanding of the contributing factors (e.g., physical chemistry, systems physiology and pharmacogenetics) and advances in quantitative modeling using mechanistic models. 2,33,5462 …”
Section: Physiology- and Population-based Pharmacokinetic Modeling (Pmentioning
confidence: 99%
“…Plasma (pCr) or serum creatinine (sCr) and blood urea nitrogen (BUN) have usually been used as indicators, or biomarkers, for kidney injury in human GPSH intoxication (El-Shenawy, 2009;Lee et al, 2008;Moon and Chun, 2010;Talbot et al, 1991;Tominack et al, 1991). Recently, several studies have suggested that pCr is not sensitive enough to detect early kidney injury or predict subsequent functional change (Sherwin et al, 2012;Toto, 1995;Vaidya et al, 2008b;Woitas et al, 2000). Other biomarkers including interleukin-18 (IL-18), cystatin-C (Cys-C), kidney injury molecule-1 (KIM-1), 2-microglobulin (2-M), albumin (Alb), neutrophil gelatinaseassociated lipocalin (NGAL) and osteopontin (Opn) have been proposed for the early and sensitive detection of AKI and functional loss Ferguson et al, 2008;Nguyen and Devarajan, 2008;Noiri et al, 2009;Vaidya et al, 2008a;Vaidya et al, 2008b), and may have greater sensitivity than pCr.…”
Section: Introductionmentioning
confidence: 99%
“…Sherwin et al [ 31 ] investigated differences in risperidone clearance between metabolic phenotypes. Decreases in relative clearance correlated with decreases in CYP2D6 metabolic activity, though no UM phenotype subjects were included in the study.…”
Section: Resultsmentioning
confidence: 99%